Localization and Translocation of MMP-2 during Aggregation of Human Platelets - Sawicki, Grzegorz; Sanders, Esmond J.; Salas, Eduardo; Wozniak, Mieczyslaw; Rodrigo, Jose; Radomski, Marek W. (Thrombosis and Haemostasis, 1998)
We have previously shown that human platelets express matrix metalloproteinase-2 (MMP-2) and that the release of this enzyme during platelet activation mediates the ADP- and thromboxane-independent part of aggregation. We have now used immunogold electron microscopy, flow cytometry, Western blot analysis and zymography methods to study the ultrastructural localization of MMP-2 in human washed platelets. Platelet aggregation was stimulated by collagen and the MMP-2 immunoreactivity of platelets was followed during various stages of aggregation. In resting platelets, MMP-2 was randomly distributed in the platelet cytosol without detectable association with platelet granules. Platelet aggregation caused the translocation of MMP-2 from the cytosol to the extracellular space. During the early stages of aggregation, MMP-2 remained in close association with the platelet plasma membrane. We conclude that the interactions of MMP-2 with platelet surface membranes mediate the aggregatory response induced by this enzyme.